Treatment of patients with herpetic infection on the principles of evidence-based medicine - H. B. Mateiko; T. V. Vepryk; N. B. Horbal (Zaporožskij Medicinskij Žurnal)
The article summarizes modern approaches to the treatment of patients with herpetic infection based on the principles of evidence-based medicine. The use of technologies and drugs in daily medical practice with proved effectiveness is the main objective of such treatment. The effectiveness of various therapeutic approaches, scientifically based principles of the treatment for patients with this pathology has been analyzed. Combined therapy of herpetic infection should be active, long and include several stages. It is important to take into account the sensitivity of different types of herpes viruses to etiotropic agents and the patient's immune response. Reducing the active replication of the virus, minimizing the likelihood of active virions transmission to the regional ganglia through the use of antiviral therapy, reduction of toxicity, elimination of additional antigenic loads are the main objectives of this treatment. Antiviral drugs - acyclovir and its analogues are used at the first stage. Prolonged intake of acyclovir in suppressive doses within 2–12 months, depending on the disease severity is initiated at the second stage of the treatment. It is also advisable to use immunotherapeutic agents, in particular, preparations of immunoglobulins, recombinant interferons, interferon inducers, while their effectiveness requires further study in modern conditions.